High-risk group and functional subtypes of non-suicidal self-injury in young adults with mental disorders - Yan, Huiru; Zhang, Yuyanan; Lu, Zhe; Li, Mingzhu; Ge, Yuqi; Mei, Dongli; Kang, Zhewei; Sun, Yaoyao; Li, Qianqian; Yan, Hao; Yang, Lei; Song, Peihua; et al. (Frontiers in Psychiatry, 2023)
Background: Identifying high-risk groups of non-suicidal self-injury (NSSI) with multiple risk factors and different functional subtypes contribute to implementing person-centered interventions. Methods: We investigated NSSI profiles among a sample of 258 psychiatric inpatients aged 18-25 years. All participants completed well-validated measures of internal personal and external environmental characteristics. One-hundred and ninety patients reported a lifetime history of NSSI and completed an additional NSSI assessment. A k-means cluster analysis was conducted to extract characteristics of risk factors and functional subtypes. Independent sample t-test, analysis of variance and χ2 test were used to test the difference of demographic statistical factors, risk factors and functional scores between groups with different frequency of NSSI. Results: The clustering of risk factors analyses supported 4-clusters. The groups with unfavorable personal and unfavorable environmental characteristics had the highest risk of repeated NSSI. Functional subtype clustering analyses supported 5-clusters. Among patients with repeated NSSI, those with depression were mainly accompanied by the “Sensation Seeking” subtype, bipolar disorder mainly supported the “Anti-suicide” subtype, and eating disorders were mostly “Social Influence” subtype. There was an interaction between functional subtypes and mental disorders. Limitations: All participants were in treatment in a psychiatric service and the results may not be generalizable to a community sample. The data included retrospective self-report which may be inaccurate due to recall bias. Conclusions: It is necessary to identify high-risk groups of NSSI who with unfavorable personal and environmental characteristics and clinical interventions need to consider the heterogeneity of patients' functional subtypes of NSSI.